Optimation Budgeting DistributionModel for Maintaining Irrigation Scheme - Sutarto Edhisono; Iwan K. Hadihardaja; Suripin Suripin (International Journal of Science and Engineering, 2016)
Utilization of palm oil  by-product such as palm fronds, leaves, empty fruit bunches (EFB), fiber fruit juice (FFJ), palm to maintenance of irrigation structures are the activities carried out routinely in irrigation areas in order to obtain optimum performance. Required costs of maintenance is provided by government based on the commanding area of irrigation area without taking into account the characteristics of each irrigation area. On the other hand the fund which is provided by the government for the purpose of maintenance of irrigation assets amounting to 40 % of the required, so that necessary special tips is needed to take optimum result of the limited funds to choose which priority irrigation structures. While this selection irrigation structures are maintained/repaired just based on policy of decision makers only. The purpose of this research was to develop an optimization model for distribution of irrigation maintenance cost allocation for the irrigation areas and  make selection to priority irrigation structures for maintenance in order to get optimum results. Location of the research is the  Pondok Irrigation Area (IA) which located in East Java province. This irrigation area  is part of the region Central River Region Solo. Pondok IA. consist of 4 irrigation areas, namely: Dero IA., Sambiroto IA., Padas IA. And Plesungan IA. The study was conducted in two stages : Stage 1 with the aim of allocating the cost of maintenance for each irrigation area in Pondok  IA., which are Dero IA., Sambiroto IA., Padas IA. And Plesungan IA. Stage 2 with the aim of making choice for the priority irrigation structures are maintained/repaired on Dero IA.,  Sambiroto IA., Padas IA. And Plesungan IA. The method used is multi criteria analysis by Analytical Hierarchy Process (AHP) with using a soft ware expert choice 2000. To complete Stage 1used multiple criteria analysis of three levels, with the top level is Pondok IA., then the second level is below, named  criterias which consists of four criterias, namely: Level of Urgency, Productivity, Commanding Area and Cost with in ratio of 4: 3: 2: 1. The lowest level  is named alternatives which consisted of four irrigation areas, namely Dero IA., Sambiroto IA., Padas IA., and Plesungan IA. The data used in this research is PAI Solo data in 2011. Stage 2 of this study is selection priority structures in each irrigation area for maintenance / repair. In this analisis is used multi-criteria analysis  also, where as the top level is the name of each irrigation area. As  criteria there are three criterias, namely: Productivity, Service area, Cost of structure with the weight of each: 3: 2: 1. As the lower level is alternative, which here are the name of the proposed structures. The proposed structures and their specifications are taken from PAI Bengawan Solo data in 2011. The structures which analysed are the structures which in very urgent and urgent condition only. The result is a list of priority irrigation structures which would be maintained from each irrigation area. Results of the  research Stage 1 : From costs available for Pondok  IA.  IDR 749,880,000.-. Dero IA., receive IDR 216,715,320.-; Sambiroto IA., receive IDR 207,716,760.-; Padas IA., receive IDR 173,222,280.-; and Plesungan IA., receive IDR 151,475,760.-. Results of the Stage 2 study is priority structures which would be maintained on each irrigation areas, namely: Dero IA., the name of the structures are: SSDOKa11, BDOKi1, BDOKa6, BDOKa15, SSDOKa14, SSDOKa15, SSDOKa17, SSDOKi1, SSDOKi2